Tayma, Saudi-Arabien. Funeräre Landschaften, Kontakte und Mobilität in der Bronzezeit Nordwestarabiens (3.–2. Jt. v. Chr.). Die Arbeiten des Jahres 2020 - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2022)
First systematic investigations in the cemeteries of Rujum Sa'sa' south of the Tayma oasis focused on the interdisciplinary excavation and analysis of Bronze Age (3rd and 2nd millennia BCE) built tombs. More than two thousands of such tombs have survived as mounds on the surface, forming an extensive burial landscape. Most of them have a circular shape, and at least two types of different chambers are attested. Rectangular graves, meanwhile, are less common. During the first season of the project (2020), excavations were conducted in six graves. 14C data from human remains from these graves cover the late 3rd to early 2nd millennium BCE. The excavations and analysis of the collapse indicate that the tombs were not designed as ›tumuli‹ but were constructed with visible facades.